FOSSIL CRICETID RODENTS FROM THE QUATERNARY OF NORTHERN BRAZIL AND THEIR PALEOENVIRONMENTAL SIGNIFICANCE (Ameghiniana, 2018)
In this study, we record and describe fossil sigmodontine rodents from the Gruta do Urso cave in the municipality of Aurora do Tocantins, Tocantins state, Northern Brazil. The sediments bearing fossils were deposited during the time spanning between 22,000 years before present (YBP) and 3,800 YBP, corresponding to the Late Pleistocene to Middle Holocene. The fossil specimens consist mostly of isolated molars and some fragments of maxillae and mandibles. We identified 12 sigmodontine taxa: Akodon sp. 1, Akodon sp. 2, Calomys sp., Holochilus sp., Kunsia tomentosus, Necromys lasiurus, Oecomys sp., Oligoryzomys sp. 1, Oligoryzomys cf. mattogrossae, Oxymycterus sp., Pseudoryzomys simplex, and Thalpomys lasiotis. This is the first fossil record for the group in Northern Brazil, and one of the largest assemblages of Pleistocene–Holocene sigmodontines registered in a single cave in the Neotropical region. Based on the diversity of the sigmodontine rodents presented herein, and on the associated fauna previously recorded from the same cave, we reconstructed the Late Pleistocene paleoenvironmental conditions of the region, similar to those of the present, as an area dominated by open vegetation formations with gallery forest patches.